CircMAP3K11 Contributes to Proliferation, Apoptosis and Migration of Human Periodontal Ligament Stem Cells in Inflammatory Microenvironment by Regulating TLR4 via miR-511 Sponging - Bohan Yu; Jiahui Hu; Qin Li; Fang Wang (Frontiers in Pharmacology, 2021)
Growing number of studies regarding the role of circRNAs in the development of various diseases have emerged in recent years, but the role of circRNAs in periodontitis pathogenesis remains obscure. Human periodontal ligament stem cells (hPDLSCs) play a critical role in periodontal remodeling, regeneration and repair processes, and their regenerative capacity could be prohibited in local periodontal inflammatory microenvironment. Herein, we sought to uncover the molecular mechanisms of periodontitis pathogenesis by investigating the role of circMAP3K11 (hsa_circ_002284) for regenerative capacity of hPDLSCs under an inflammatory condition. The hPDLSCs isolated from periodontitis patients were used as a cell model of inflammatory microenvironment to study the effect of the circMAP3K11/miR-511-3p/TLR4 axis on the proliferation, apoptosis and migration of hPDLSCs under inflammatory conditions. Compared to the periodontal tissues from normal subjects, those from periodontitis patients exhibited higher expression levels of circMAP3K11 and TLR4, and lower expression level of miR-511-3p. Both the expressions of circMAP3K11 and TLR4 were negatively correlated with the expressions of miR-511-3p in periodontitis. In vitro studies demonstrated that circMAP3K11 is capable of enhancing hPDLSCs proliferation and migration, and reducing the apoptosis of hPDLSCs. We also found that circMAP3K11 could up-regulate the expression of transcription factors that are closely related to periodontal regeneration (Runx2, OSX, ATF4, and BSP). RT-PCR and western blot showed that the inhibitory role of miR-511-3p on TLR4 expression could be reversed by circMAP3K11, which was in line with the results of bioinformatics tools and luciferase reporter assay. Meanwhile, both in vitro and in vivo studies indicated that circMAP3K11 could reverse the effects of miR-511-3p in periodontitis, which further confirmed that circMAP3K11 functioned as a ‘sponge’ of miR-511-3p to positively regulate the expression of TLR4. Taken together, our study preliminarily uncovered a circMAP3K11/miR-511-3p/TLR4 axis that regulates the function of hPDLSCs in periodontitis, providing novel insight and scientific base in the treatment of periodontal tissue regeneration based on stem cells.